2019
DOI: 10.1534/g3.119.400452
|View full text |Cite
|
Sign up to set email alerts
|

GWAS for Meat and Carcass Traits Using Imputed Sequence Level Genotypes in Pooled F2-Designs in Pigs

Abstract: In order to gain insight into the genetic architecture of economically important traits in pigs and to derive suitable genetic markers to improve these traits in breeding programs, many studies have been conducted to map quantitative trait loci. Shortcomings of these studies were low mapping resolution, large confidence intervals for quantitative trait loci-positions and large linkage disequilibrium blocks. Here, we overcome these shortcomings by pooling four large F2 designs to produce smaller linkage disequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 59 publications
3
48
0
Order By: Relevance
“…Zhou et al reported the BMP2 gene as a candidate gene associated with body length and body height traits in Chinese Shushan pigs ( Zhou et al, 2019 ). Moreover, BMP2 as a candidate gene was discovered and associated with carcass length in pigs ( Falker-Gieske et al, 2019 ). BMP2 was also associated with the distal midpiece reflex for sperm traits in a Duroc boar population ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al reported the BMP2 gene as a candidate gene associated with body length and body height traits in Chinese Shushan pigs ( Zhou et al, 2019 ). Moreover, BMP2 as a candidate gene was discovered and associated with carcass length in pigs ( Falker-Gieske et al, 2019 ). BMP2 was also associated with the distal midpiece reflex for sperm traits in a Duroc boar population ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…GWAS were performed with the Genome-wide Complex Trait Analysis (GCTA) software version 1.92.3 beta3 using the imputed sequence level genotype data filtered for MAF (> 0.01). In order to correct for relatedness between animals and stratification [ 6 ], a random genetic term was included based on a genomic relationship matrix calculated only from SNP-chip-data and following a leave one chromosome out (LOCO) approach as described here [ 10 ]. Briefly, a model of the form y = Wα + Xβ + u + ϵ is fitted, where y is an n × 1 vector of phenotypes n hens (a summary of the phenotype data is shown in Table 5 ).…”
Section: Methodsmentioning
confidence: 99%
“…Here we present an approach in which we performed whole-genome sequencing (WGS) on selected animals, in order to impute low-level chip genotype data to sequencing level. We have already successfully applied this strategy in a porcine F2 design [10]. In the present study, we combined the results of GWAS from two resource populations: an F2 design and one half-sib (HS) population divergently selected for feather pecking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association study (GWAS) is an effective strategy to examine the underlying genetics of complex traits [12]. Many studies have identified candidate markers associated with important economic traits in pigs, such as meat quality [13] and growth [14] . For litter weight gain trait in Yorkshire sow lactation, the GWAS has been performed to detect two quantitative trait locus (QTLs) on Sus scrofa Chromosome (SSC) 7 (126Mb and 101Mb) [15].…”
Section: Introductionmentioning
confidence: 99%